2006
DOI: 10.1210/en.2005-0984
|View full text |Cite
|
Sign up to set email alerts
|

Both Testosterone and Follicle-Stimulating Hormone Independently Inhibit Spermatogonial Differentiation in Irradiated Rats

Abstract: Simultaneous suppression of both testosterone and FSH with GnRH antagonists (GnRH-ant) reverses the radiation-induced block in spermatogonial differentiation in F1 hybrids of Lewis and Brown-Norway rats. Although addition of exogenous testosterone restores the block, it also raises FSH, and hence it had not been possible to conclusively determine which hormone was inhibiting spermatogonial differentiation. In the present study, we establish the relative roles of testosterone and FSH in this inhibition using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
0
31
2
Order By: Relevance
“…Rat serum FSH and LH levels were measured using immunofluorometric assays (Delfia; PerkinElmer Wallac) [22,23,29,30]. Serum E2 was measured using an anti-E2 antibody, double-antibody radioimmunoassay kit (catalog no.…”
Section: Hormone Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat serum FSH and LH levels were measured using immunofluorometric assays (Delfia; PerkinElmer Wallac) [22,23,29,30]. Serum E2 was measured using an anti-E2 antibody, double-antibody radioimmunoassay kit (catalog no.…”
Section: Hormone Measurementsmentioning
confidence: 99%
“…However, this block was slowly reversed by treatment with GnRH-ant and flutamide, which suppresses intratesticular testosterone (ITT) and gonadotropin levels and inhibits testosterone action [21,22]. Further studies showed that ITT (and, to a lesser extent, FSH) primarily was responsible for the inhibition of differentiation in this system [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, recovery of spermatogonial proliferation is blocked by testosterone following cytotoxic damage to the testis in rats from multiple toxicants including radiation (Meistrich & Shetty 2003, Shetty et al 2006a. In addition, FSH also blocks spermatogonial proliferation independently of testosterone following irradiation.…”
Section: Testosterone Regulation Of Spermatogoniamentioning
confidence: 99%
“…Rat serum FSH and LH levels were measured using immunofluorometric assays (Delfia; PerkinElmer Wallac) [22,23,29,30]. Serum E2 was measured using an anti-E2 antibody, double-antibody radioimmunoassay kit (catalog no.…”
Section: Hormone Measurementsmentioning
confidence: 99%
“…However, this block was slowly reversed by treatment with GnRH-ant and flutamide, which suppresses intratesticular testosterone (ITT) and gonadotropin levels and inhibits testosterone action [21,22]. Further studies showed that ITT (and, to a lesser extent, FSH) primarily was responsible for the inhibition of differentiation in this system [23].…”
Section: Introductionmentioning
confidence: 99%